Pru p 3‐Epitope‐based sublingual immunotherapy in a murine model for the treatment of peach allergy. Issue 10 (6th September 2017) - Rodriguez, Maria J.; Mascaraque, Ainhoa; Ramos‐Soriano, Javier; Torres, Maria J.; Perkins, James R.; Gomez, Francisca; Garrido‐Arandia, Maria; Cubells‐Baeza, Nuria; Andreu, David; Diaz‐Perales, Araceli; Rojo, Javier; Mayorga, Cristobalina
Abstract : Scope: Food‐specific immunotherapy (SIT) is a promising treatment for lipid transfer protein (LTP)‐syndrome. We propose a novel sublingual‐SIT (SLIT) that combines a Pru p 3 T‐cell peptide and an oligodeoxyribonucleotide (ODN) with CpG motifs (ODN‐CpG) as adjuvants to induce a specific Th1/Treg response. Methods and results: LTP‐peach allergic mice were treated sublingually with a combination of a CpG sequence and mono‐ or tetravalent systems including a Pru p 3 peptide, D1 (Prup3) or D4 (Prup3). Mice were challenged intraperitoneally with Pru p 3 one or three weeks after SLIT and tolerance was assessed. Mice treated with D1 (Prup3)+CpG were protected from anaphylaxis after Pru p 3 challenge. They showed no change in body temperature, lower levels of Pru p 3‐specific IgE and IgG1 antibodies and higher levels of sIgG2a compared to the untreated group. They had fewer IgE and IgG1 secreting cells and more sIgG2a secreting cells. Moreover, a significantly lower number of Pru p 3‐specific CD4 + T cells and a higher number of Treg cells were found, alongside a Th1 cytokine pattern. These changes were maintained for three weeks after stopping treatment. Conclusion: D1 Prup3+CpG represents a promising SIT for food allergy. It is easily synthesized and induces protection from anaphylaxis to Pru p 3 that is maintained for at least three weeks. Abstract : In this study, LTP‐peach anaphylactic mice are treated sublingually with a combination of a CpG sequence and mono‐ or tetravalent systems including a Pru p 3 peptide. It is found that the monomeric compound administered sublingually represents a promising specific immunotherapy for food allergy since it is easily synthesized, safe, and induces a persistent protection from anaphylaxis to Pru p 3.